PSYCHOLOGICAL WELL-BEING OF STUDENTS IN HIGHER EDUCATION INSTITUTIONS (2025)
The book Psychological Well-being of Students in Higher Education Institutions provides a comprehensive exploration of the psychological challenges faced by students in Malaysian universities, particularly during the transition to online learning amid the COVID-19 pandemic. Addressing increased academic demands, social isolation, and technology dependency, the book delves into the effects of these factors on student well-being. It covers topics such as stress, well-being, perfectionism, social comparison, motivation, learning strategies, and personality with each chapter offering insights into different aspects of psychological resilience and mental health. It explores the effects of the PERMA model including positive emotion, engagement, relationships, meaning, and accomplishments on student happiness and propose solutions to enhance resilience. As students adapt to using technology for educational purposes and familiarize themselves with online assessments, they face increased academic workloads and pressure to meet assignment deadlines. This can lead to heightened stress levels and feelings of being overwhelmed. Hence, this book is a vital resource for university students, educators or lecturers, parents, and policymakers, aiming to foster supportive environments and effective strategies for improving the mental health and academic success of students facing modern educational challenges​.